2013
DOI: 10.1891/0730-0832.32.6.399
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for NICU Discharge: Mothers’ Concerns

Abstract: The mothers expressed confidence in their ability as a caregiver but expressed concern about being tired, the need for readmission to the hospital, and missing a change in the infant's conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 15 publications
2
44
0
Order By: Relevance
“…In average, the mothers participating in the study needed seven weeks to start feeling comfortable and secure to take care of their infants at home, after the return of their children from the neonatal unit. Such findings are similar to those described by other researchers, who report the difficulties mothers undergo to establish a bond with their children when they do not have a close contact with them right after their birth; 1,4,7 , the feeling of impotence toward caring for the child at home after the infant is discharged from the hospital; [5][6]8,10 the doubts and uncertainties as to how to perform some care activities and how to modify them as the baby grows and changes, as well as the feeling of not being a real mother but a fearful person that is incapable of taking care of her child without the support of healthcare professionals. [4][5][6][14][15][16] Throughout the pre and postnatal period, the professional nurse is recognized as the one being in more contact with the woman.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In average, the mothers participating in the study needed seven weeks to start feeling comfortable and secure to take care of their infants at home, after the return of their children from the neonatal unit. Such findings are similar to those described by other researchers, who report the difficulties mothers undergo to establish a bond with their children when they do not have a close contact with them right after their birth; 1,4,7 , the feeling of impotence toward caring for the child at home after the infant is discharged from the hospital; [5][6]8,10 the doubts and uncertainties as to how to perform some care activities and how to modify them as the baby grows and changes, as well as the feeling of not being a real mother but a fearful person that is incapable of taking care of her child without the support of healthcare professionals. [4][5][6][14][15][16] Throughout the pre and postnatal period, the professional nurse is recognized as the one being in more contact with the woman.…”
Section: Discussionsupporting
confidence: 90%
“…6,[8][9] Hence, healthcare professionals should recognize these facts and offer parents of hospitalized newborn babies the place they deserve to be with their children. 10 The aim of this study is to describe how mothers who are submitted to stressors, such as the separation from their children and restricted participation in the care for their babies during the hospitalization process at the NICU, experience the care for the infants at home. The study will describe the process experienced by mothers toward building the confidence and the assurance that they will be able to provide their infants the love and necessary care to keep them away from the hospital and growing healthy.…”
Section: Introductionmentioning
confidence: 99%
“…In similar study of Patil, (2014) showed slightly different results. Assessing the mothers stress they found 70% had moderate stress and 30% had severe stress, while no mothers with mild stress were present.…”
Section: Resultsmentioning
confidence: 78%
“…Preterm infants usually require additional care and support post-discharge, because of health and developmental problems related to their immaturity (Hutchinson, Spillet, & Cronin, 2012). Further, factors that cause parental stress about bringing the infant home inhibit the bonding process (Aagaard et al, 2015;Browne and Talmi, 2005); these include high medical needs, the length of hospitalization, and a lack of knowledge about the infant's condition and development (Patil, 2014;Segre et al, 2015). Olshtain-Mann & Auslander (2008) have also reported on the ongoing stress after returning home.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation